Pseudomonas aeruginosa pqs Quorum Sensing Mediates Interaction with Mycobacterium abscessus In Vitro - Yun Long; Zhi Li; Menglu Li; Peiyi Lu; Yujia Deng; Pengyao Wu; Xue Li; Gangjian Qin; Jiamin Huang; Wenying Gao; Guobao Li; Tianyuan Jia; et al. (Microorganisms)
Pseudomonas aeruginosa and Mycobacterium abscessus are opportunistic pathogens that cause severe infections in hospitals, and their co-infections are increasingly reported. The interspecies interactions between these two bacterial species and their potential impacts on infections are largely unexplored. In this study, we first demonstrated that P. aeruginosa inhibits the growth of M. abscessus by iron chelating via pqs quorum sensing. Next, through proteomic analysis, we discovered that the PQS molecule significantly changed a large amount of protein expression in M. abscessus, including proteins involved in the type VII secretion system and iron homeostasis. Furthermore, we revealed that PQS significantly enhanced the production of bacterial membrane vesicles (MVs) by M. abscessus. Our study suggests that the P. aeruginosa PQS can serve as an interspecies signaling molecule to communicate with Mycobacterium and affect their physiology and virulence.